The impact of exercise and diet on body composition and biochemical parameters of blood - a case study - Filarecka, Agnieszka; Biernacki, Maciej; Kuczma, Monika; Każimierczak, Paweł; Każimierczak, Rafał (Journal of Education, Health and Sport, 2019)
Obesity is Jena of the most common diseases of civilization twenty-first century. Affects people of all ages, it carries a number of complications, not only in terms of physical and mental health. I estimate that obese people have a greater sociological problems, and the level of self-acceptance in these individuals is much lower. Ways to deal with the problem of obesity are many, but one of the most effective physical activity is combined with diet. Epidemiological studies confirm the beneficial effect of physical activity to reduce the risk of obesity and its impact on the comprehensive treatment. Increasing energy expenditure affects not only the reduction of body fat. Regular physical activity increases muscle tissue and bone, and a decrease in resting and exercise blood pressure, pulse. Through physical activity, we are able to influence the lipid profile and glucose tolerance. Adaptation of physical activity should be an individual, it is recommended to increase daily physical activity for 30 minutes.The unit training should increase energy expenditure by 300 - 400kcal. Coexistence of diseases in obesity is a major limiting factor for some physical activity, however, there are forms of relieving traffic using such a resistance. Exercises in water or a bike.Objective: Effects of exercise and diet on body weight change in the composition and the results of biochemical blood.Methods: Case study of women - 40 years, BMI 36.06, a man - 39 years, BMI 46.69, using the same physical activity and diet throughout the year. Used in the study of body composition, performed every month, and the results of biochemical blood made prior to physical activity after switching diets, and after a year.Case study :To describe the changes in body composition under the influence of exercise and diet used a man and woman - marriage. The study lasted one year. Physical activity in both people was the same (frequency - 5 times a week). The diet consisted of the exclusion of sugar and fruits, junk food, highly processed foods. Eating regular meals. Both individuals are working as a sales representative. A woman born in 1976, 164 cm tall, 97 kg output. The man born in 1977, 178 cm tall 148kg weight output. In women, there were no chronic diseases in the male there is asthma and hypertension.Results: For one year body composition has changed significantly. In women reported weight loss of 33kg, U man of 51 kg. Loss of body fat in women was 35 kg and 2 kg gain muscle mass.One man, a decrease of 63 kg body fat to 16 kg and 4 kg increase in muscle mass. Blood biochemical parameters in both cases, have changed. Total cholesterol decreased in women with 288 mg / dl to 152 mg / dl in men with 325mg / dl to 157 mg / dl. In both sexes increased level of self-acceptance, mental health and general well-being. Additionally, in men increased capacity (FVC), and the blood pressure is normalized.Conclusions: Physical activity and diet changes the composition of body weight. The combination of exercise and diet affect the results of biochemical blood, normalization of blood pressure and asthma. Physical activity and diet is the prevention of diabetes, hypertension. The elimination of sugars and fruits is an effective method to reduce body fat. Weight loss is not linear. Physical activity affects the growth of muscle tissue.